2017
DOI: 10.1093/cid/cix166
|View full text |Cite|
|
Sign up to set email alerts
|

Lessons Learned at the Epicenter of Brazil’s Congenital Zika Epidemic: Evidence From 87 Confirmed Cases

Abstract: Congenital Zika virus infection has stimulated great international concern. A prospective case series of 87 infants with laboratory-confirmed congenital Zika syndrome (CZS) at the epicenter of the Brazilian Zika epidemic in Pernambuco state is presented. Mothers were interviewed for symptoms of possible Zika virus (ZIKV) infection during pregnancy, and fetal ultrasounds were obtained. Infant cerebrospinal fluid (CSF) samples were tested for ZIKV-specific antibodies, and sera were screened for other congenital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 27 publications
6
87
1
2
Order By: Relevance
“…In May 2015, the first case of ZIKV infection was reported in Brazil [13] and the virus rapidly spread throughout the country and much of Latin America, causing the largest recorded epidemic of the virus to date [14]. The Brazilian epidemic raised great international concern because of severe birth defects, including microcephaly, in neonates born to mothers infected by ZIKV during pregnancy [3,15,16].ZIKV is transmitted mainly through the bite of infected mosquitoes from the genus Aedes, although other vectors may also be involved in the transmission [17][18][19][20][21]. Additionally, other routes of ZIKV transmission have been identified, including blood transfusions, transplacental, perinatal, and sexual intercourse [22][23][24].…”
mentioning
confidence: 99%
“…In May 2015, the first case of ZIKV infection was reported in Brazil [13] and the virus rapidly spread throughout the country and much of Latin America, causing the largest recorded epidemic of the virus to date [14]. The Brazilian epidemic raised great international concern because of severe birth defects, including microcephaly, in neonates born to mothers infected by ZIKV during pregnancy [3,15,16].ZIKV is transmitted mainly through the bite of infected mosquitoes from the genus Aedes, although other vectors may also be involved in the transmission [17][18][19][20][21]. Additionally, other routes of ZIKV transmission have been identified, including blood transfusions, transplacental, perinatal, and sexual intercourse [22][23][24].…”
mentioning
confidence: 99%
“…The existing literature has identified some potential risk factors, mainly through animal studies and case reports, that we did not find among NBDPS cerebellar hypoplasia cases. Several studies, reviews, and case reports have found associations between prenatal infections, particularly viral infections, and cerebellar hypoplasia (Ceballos et al, ; de Fatima Vasco Aragao et al, ; Hazin et al, ; Koning et al, ; Melo et al, ; Meneses et al, ; Patel & Barkovich, ; Poretti, Wolf, & Boltshauser, ; Steinlin et al, ). Yet, the possible role of an infectious etiology remains unclear from our NBDPS results.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of evidence for potential prenatal risk factors comes from animal studies or case reports (Koning et al, ; Poretti et al, ), although Zika virus infection has drawn attention to the posterior fossa, including cerebellar hypoplasia. Maternal exposures linked to cerebellar hypoplasia include smoking (Ekblad et al, ), alcohol use (Norman, Crocker, Mattson, & Riley, ), cocaine use (Bellini, Massocco, & Serra, ), valproic acid use (Main & Kulesza, ; Squier, Hope, & Lindenbaum, ), mifepristone use for failed termination (Afadapa & Elsapagh, ; Sitruk‐Ware, Davey, & Sakiz, ), family history (Hunter, ; Murray, Johnson, & Bird, ), and congenital infections (Silasi et al, ) such as cytomegalovirus infection (Ceballos, Ch'ien, Whitley, & Brans, ; Patel & Barkovich, ; Poretti et al, ; Steinlin, Nadal, Eich, Martin, & Boltshauser, ), and Zika virus infection (Araujo Junior, Carvalho, Tonni, & Werner, ; de Fatima Vasco Aragao et al, ; Hazin et al, ; Melo et al, ; Meneses et al, ; Schuler‐Faccini et al, ). In addition, gestational age at birth has been associated with cerebellar hypoplasia and several studies have focused on postnatal risk factors for the maturation of the cerebellum after preterm birth, including glucocorticoid exposure and brain injury (Brossard‐Racine et al, ; Limperopoulos et al, ; Tam, ; Tam et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Zika virus IgM antibodies have been detected in the cerebrospinal fluid in a microcephalic infant as evidence of ZIKV being the causative agent of microcephaly [33,34]. Hughes et al [35] found persistent infection in immature neuronal tissues.…”
Section: Pathogenesismentioning
confidence: 99%